2006
DOI: 10.1016/j.ymgme.2006.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of drug delivery to bone: Characterization of human tissue-nonspecific alkaline phosphatase tagged with an acidic oligopeptide

Abstract: Hypophosphatasia is caused by deficiency of activity of the tissue-nonspecific alkaline phosphatase (TNSALP), resulting in a defect of bone mineralization. Enzyme replacement therapy (ERT) with partially purified plasma enzyme was attempted but with little clinical improvement. Attaining clinical effectiveness with ERT for hypophosphatasia may require delivering functional TNSALP enzyme to bone. We tagged the C-terminal-anchorless TNSALP enzyme with an acidic oligopeptide (a six or eight residue stretch of L-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…Pathological lesions in CIA appear not only in bone but also in synovial tissue, which does not contain HA. Consistent with the previous studies (27,28), acidic oligopeptide-tagged esRAGEs, including D 6 -esRAGE, were localized to a mineralized region in bone, where they were retained for over 1 week. The principle of bone-targeting by using an acidic oligopeptide is based on the affinity between negatively charged acidic oligopeptide and positively charged calcium in HA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Pathological lesions in CIA appear not only in bone but also in synovial tissue, which does not contain HA. Consistent with the previous studies (27,28), acidic oligopeptide-tagged esRAGEs, including D 6 -esRAGE, were localized to a mineralized region in bone, where they were retained for over 1 week. The principle of bone-targeting by using an acidic oligopeptide is based on the affinity between negatively charged acidic oligopeptide and positively charged calcium in HA.…”
Section: Discussionsupporting
confidence: 90%
“…A significant difference between acidic oligopeptide-tagged esRAGEs was not observed in the biodistribution. In addition, it is likely that a longer stretch of acidic oligopeptide affects physiological properties, except for biodistribution of esRAGE, because Nishioka et al (27) demonstrated that the longer stretch of acidic oligopeptide more largely changed the N-linked oligosaccharides structure of glycoprotein. The ligand-binding V-domain of RAGE contains two potential N-glycosylation sites, and the N-linked oligosaccharides on RAGE are suggested to mediate the interaction with its ligands (20,21).…”
Section: Biodistribution Of Untagged and Acidic Oligopeptide-tagged Ementioning
confidence: 99%
See 1 more Smart Citation
“…Kasugai et al, 2000 showed that they could enhance estradiol uptake by bone and prevent osteoporosis by tagging the hormone to Glu 6 (E6) [75,76]. We and others have recently applied this new bone-targeting system to a large molecule, an enzyme (tissue nonspecific alkaline phosphatase), showing that the tagged enzymes are delivered more efficiently to bone [77][78][79] and that the tagged enzyme improves clinical and pathological effects of a mouse model of a systemic bone disease, hypophosphatasia, better than untagged native enzyme [80]. Human Nacetylgalactosamine-6-sulfate sulfatase (GALNS) and ß-glucuronidase (GUSB) have also been bioengineered to add E6 and D6.…”
Section: Long Circulating Ert-a Chemically Modified β-Glucuronidase (mentioning
confidence: 99%
“…63,64 The authors of this present paper and others have recently attached this novel bone-targeting peptide to an enzyme (tissue nonspecific alkaline phosphatase) and shown that the tagged enzyme is delivered more specifically to bone than unmodified enzyme, improving the clinical and pathological consequence of the systemic bone disease, hypophosphatasia. 65,66 Human GALNS has also been bioengineered to add a hexa-glutamate sequence (E6) to its N-terminus (E6-GALNS). This tagged enzyme has a markedly reduced rate of clearance from the circulation, increasing blood levels 20 times higher than that of the untagged enzyme.…”
Section: Ertmentioning
confidence: 99%